The cytoplasmic N-terminal tail of Zika virus NS4A protein forms oligomers in the absence of detergent or lipids - Wahyu Surya; Yiting Liu; Jaume Torres (Scientific Reports, 2023)
Abstract The non-structural (NS) NS4A protein in flaviviruses has three predicted transmembrane domains, is critical for virulence and participates in membrane morphogenesis. In Dengue virus (DENV), both hydrophylic N-terminal tail and its first transmembrane domain participate in the formation of oligomers which are important for pathogenicity. However, the relative importance of the N-terminal domain in oligomerization has been under debate. In particular, since in the absence of detergent or lipids, this domain (residues 1–48) in both DENV and Zika virus (ZIKV) NS4A, was found to be disordered. Recently, however, we reported preliminary data that showed that peptide ZIKV NS4A 4–58 adopts a defined secondary structure in aqueous solution and forms oligomers, signaling its importance for full length NS4A oligomerization. Herein we have performed detailed analytical ultracentrifugation experiments to further characterize the oligomerization of this peptide and also a shorter variant (residues 4–44). In both cases, sedimentation velocity produced a single species with concentration-dependent sedimentation coefficient, consistent with a fast equilibrium between at least two species. Combining sedimentation velocity and equilibrium experiments, data is best fitted to a monomer–dimer–trimer equilibrium. Possible models of NS4A oligomers obtained with AlphaFold-2 predict the stabilizing role for residues in this N-terminal domain, such as Arg20, Asn27, Ala44 and Glu50, all at highly conserved positions in flavivirus NS4A proteins. Our results are thus consistent with N-terminal domain interactions acting as one of the driving forces for NS4A homo-oligomerization.